2012
DOI: 10.1111/j.2045-0648.2012.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

The non-compliant client

Abstract: : The issue of owner compliance – or lack thereof – is a wide‐ranging problem through all genres of veterinary medicine and, indeed, medicine worldwide. This article provides a discussion of issues commonly presented in relation to client compliance in the UK, and compares and contrasts these problems with issues in human medicine and in veterinary medicine around the world. Protocols are then presented to improve compliance within veterinary medicine, through the use of a diverse range of communication channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Participating veterinarians expressed uncertainty around whether clients utilize the information provided in handouts [ 11 ] and participating pet owners expressed the need to ask questions and clarify information received from handouts after their appointment. If veterinarians do not provide an opportunity for clients to ask questions about information received from handouts, veterinarians may assume that the information is not useful for the client, yet a lack of written information has been associated with reduced client compliance [ 26 ]. Additionally, the absence of follow-up telephone calls from veterinarians may further reduce client compliance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participating veterinarians expressed uncertainty around whether clients utilize the information provided in handouts [ 11 ] and participating pet owners expressed the need to ask questions and clarify information received from handouts after their appointment. If veterinarians do not provide an opportunity for clients to ask questions about information received from handouts, veterinarians may assume that the information is not useful for the client, yet a lack of written information has been associated with reduced client compliance [ 26 ]. Additionally, the absence of follow-up telephone calls from veterinarians may further reduce client compliance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…If veterinarians do not provide an opportunity for clients to ask questions about information received from handouts, veterinarians may assume that the information is not useful for the client, yet a lack of written information has been associated with reduced client compliance [ 26 ]. Additionally, the absence of follow-up telephone calls from veterinarians may further reduce client compliance [ 26 ]. These results emphasize the importance of providing clearly written information to clients and even more so the importance of providing a plan for following up with a client or letting clients know they can contact the veterinary team as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Getting pet owners to adhere to veterinary ectoparasite protection recommendations is not easy. Studies on human patient adherence to prescribed treatment regimens have shown that simpler, less frequent dosing regimens improve patient compliance across a variety of therapeutic classes [ 44 – 46 , 49 , 50 , 54 57 ]. In veterinary medicine, adherence to veterinary prescribed dosing intervals tends to be better when dosing is less frequent with extended dosing intervals [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in the UK suggested that only 37 per cent of clients has shown full compliance with the medicines or follow-up practices recommended by the veterinarian. It has been revealed that approximately 70-85 percent of patient owners give only one-third of the required doses on time (Loftus, 2012).…”
Section: Alternative Medication Delivery Methodsmentioning
confidence: 99%